Comparison of Antiretroviral Regimens: Adverse Effects and Tolerability Failure that Cause Regimen Switching - Kim, Min Jung; Kim, Shin-Woo; Chang, Hyun-Ha; Kim, Younjoo; Jin, Sun; Jung, Hyejin; Park, Jung Hwa; Kim, Sujeong; Lee, Jong Myung (Infection & chemotherapy, 2015)
The efficacy of antiretroviral therapy (ART) has improved, and the adverse effects of antiretroviral drugs have been reduced. However, these adverse effects still significantly influence patient compliance, increasing the risk of tolerability failure. Therefore, we investigated the adverse effects and tolerability failure causing changes in the first ART regimen, and identified the regimens that were most vulnerable to switching. We enrolled patients with human immunodeficiency virus (HIV) who commenced their first ART between January 1, 2011 and July 30, 2014. Patients who started their first ART regimen at the Kyungpook National University Hospital were included in the study if they were aged ≥18 years and were followed-up for ≥12 weeks. The primary dependent variable was the duration of treatment on the same ART regimen. We analyzed the maintenance rate of the first ART regimen based on the treatment duration between these groups using survival analysis and log rank test. The frequency of the adverse effects of ART regimens was analyzed by multiple response data analysis. During the investigation period, 137 patients were enrolled. Eighty-one patients were maintained on the initial treatment regimen (59.1%). In protease inhibitor (PI)-based regimen group, 54 patients were maintained on the initial treatment regimen (54/98, 55.1%). In non-nucleoside reverse transcriptase inhibitor (NNRTI)-and integrase inhibitor (II)-based regimen group, 15 (15/26, 57.7%) and 12 (12/13, 92.3%) patients were maintained on the initial treatment regimen, respectively. Adverse effects that induced ART switching included rash (16/35, 45.7%), gastrointestinal discomfort or pain (7/35, 20%), diarrhea (7/35, 20%), hyperbilirubinemia (6/35, 17.1%), headache or dizziness (3/35, 8.5%). Among the treatment regimens, the group receiving an II-based regimen showed the least switching. The group receiving PI-and NRTI-based regimens were most likely to switch due to adverse effects during the early treatment period. However, after about 18 months, switching was rarely observed in these groups. Among the PI drugs, darunavir/ritonavir showed fewer drug changes than atazanavir/ritonavir (P = 0.004, log rank test) and lopinavir/ritonavir (P = 0.010). Among the NNRTI drugs, rilpivirne produced less switching than efavirenz (P = 0.045). Adverse effects to ART resulted in about a quarter of patients switching drugs during the early treatment period. II-based regimens were advantageous because they were less likely to induce switching within 18 months of treatment commencement. These findings indicated the importance of considering and monitoring the adverse effects of ART in order to improve adherence.